Biomehanika analiza smea iz prednje i straznje zone u odbojci l - Durkovic, T.; Marelic, N.; Hraski, Z.; Sikanja, L. (Croatian Sports Medicine Journal, 2005)
In volleyball today, spike is becoming more and more important as a attack element. It makes the game more exciting and adds to a variety of attack moves. The aim of this thesis is to make a comparative analysis of two basic techniques: spike from the net and back row spike, performed by a National Volleyball League Player. Two cameras recorded the spikes, with a frequency of 60 shots per second. Dana was digitalised and processed in accordance with the APAS standard procedure. The obtained results justify the tendency to increase the back row attack and give the coaches a clearer picture of the difference between the two spikes.